558 A Surface Electrode Adjacent to Vagal Nerve Stimulator Lead Can Aid in Characterizing VNS Mediated Sleep Disordered Breathing. (3rd May 2021) - Chan, Jeremy; Wrede, Joanna
Abstract: Introduction: Vagal nerve stimulators (VNS) are a nonpharmacological treatment for patients with refractory epilepsy. The VNS can decrease seizure frequency by over 75% in 40% of pediatric patients with refractory epilepsy. An underrecognized side effect is sleep disordered breathing (SDB). The purpose of this study was to demonstrate how a sensor placed adjacent to the VNS lead can distinguish whether SDB is due to VNS discharge. Methods: Five pediatric patients (ages: 5–8) with refractory epilepsy with VNS were referred to our sleep center for concern for SDB. Each patient underwent a polysomnogram (PSG) that included a standard PSG montage with a surface electrode placed adjacent to their left lateral neck to detect VNS discharge. VNS associated apnea hypopnea index (vAHI) was calculated by determining the number of hypopneas and obstructive apneas occurring during VNS discharge. Results: Of the 5 patients, three met pediatric criteria for obstructive sleep apnea (OSA). Patient 1 had an obstructive AHI (oAHI) of 21.3 events/hr with a vAHI accounting for 79% of the total (16.8 events/hr), patient 2 had an oAHI of 16.6 events/hr with a vAHI accounting for 57% of the total (9.5 events/hr), and patient 3 had an oAHI of 1.9 events/hr with vAHI accounting for 68% of the total (1.3 events/hr). Because of these findings, the VNS settings of all 3 patients were changed with the goal of reducing SDB due to VNS discharge. Upon repeat PSG, patient 2 had reduced OSA with an oAHI of 3 events/hr, with no events associated with VNS discharge. The remaining 2 patients did not exhibit VNS associated SDB, however, both experienced increased respiratory rate during VNS discharge. Conclusion: We demonstrated that a surface electrode adjacent to the VNS is able to temporally co-register VNS discharges and enabled us to directly correlate SDB to VNS stimulation in 3 patients with refractory epilepsy. Because of our findings, we titrated the VNS parameters in all 3 patients, with one showing resolution of VNS associated SDB on repeat PSG. We propose that an added surface electrode to detect VNS discharge be considered as standard practice in PSG studies of patients with VNS. Support (if any):